KEDUDUKAN PERKAWINAN SEMARGA DALAM KLAN SEMBIRING PADA MASYARAKAT KARO DI DESA TANJUNG PULO KECAMATAN TIGA NDERKET KABUPATEN KARO - ARIE GANTI (PREMISE LAW JURNAL, 2017)
It has been known in the Karonese community there is a prohibition to getmarried with the same clan. The objective of this research was to analyze theposition of marriage in the same Sembiring clan in the Karonese community atTanjung Pulo Village, Tiga nderket Subdistrict, Karo Regency. The formula of theproblems was the reasons why it was allowed, the position, and its consequence.The research used empirical juridical normative and descriptive analytic method.Primary legal materials were Law No. 1/1974 on Marriage, the result of theinterviews with the adat Karonese community, while secondary data wereobtained from books and tertiary legal materials such as dictionaries, anddictionaries on law. The result of the research shows that the reasons why gettingmarried with the same Sembiring clan is allowed are religion and the change insocial values. It is considered legitimate and recognized when the stages of itsprocedures have been done such as belo selambar (proposal), nganting manuk(negotiation on marriage ceremony), kerja nereh empo (adat party), and mukul(its legitimation). Sembiring and Perangin-angin clans are specifically calledlimited eleutherogamy; that is, a person from a certain clan in Sembiring andPerangin-angin clans is allowed to get married with a person of the same subclanin different clan. The legal consequence if getting married with sameSembiring clan is the existence of sinereh (wife) will break off from her family.When the parents die, the brother of the late father takes the responsibility toraise the children, joint property will be property grouping, and Sembiring clanwill be attached to the children who inherit it from their father and mother.Keywords: Marriage with Same Clan, Karonese Adat, Sembiring Clan.